Analisis Kebutuhan Rancang Bangun Multimedia Pembelajaran Materi Listrik Dinamis - Dede Solihudin; Afrizal Mayub; Sutarno Sutarno (Departement of Mathematics Education, 2023)
Dynamic electricity material is material that requires more understanding so that the learning process can run well, in need of a media that is able to encourage and assist the student learning process. The purpose of this study is to analyze the needs of teachers and students for the design of learning multimedia for the science learning process of dynamic electricity material at SMPN 29 Kaur. This study is a descriptive type of research with a quantitative approach.. The sampling technique in this study used a non-probability sampling technique with a saturated sampling technique method and a sample of 32 respondents were students and science teachers. Based on the results of the questionnaire analysis provided, it was found that 100% of teachers and 95% of students supported the design of learning multimedia as a learning resource for dynamic electricity material